The Principle of Guardianship in Marriage: A Philosophical Analysis of the Harmonization of Islamic Law and Indonesian Positive Law - Muhammad Husni Abdulah Pakarti; Aden Rosadi; Usep Saepullah; Husain (An-Nisa: Journal of Islamic Family Law, 2025)
Guardianship in marriage law has an important position as one of the conditions for the validity of marriage in the perspective of Islamic law and also received recognition in the Indonesian national legal system. However, the application of guardianship principles in the context of positive law often raises debates, especially regarding the authority of the guardian, the position of women, and the limits of state intervention. This study aims to examine the principles of guardianship in the Indonesian marriage law system and its relevance to the values of justice and legal protection. This research uses a normative juridical approach with a literature study method. Sources of data are obtained from legislation, legal doctrine, and relevant court decisions. The analysis is done descriptively-qualitatively by tracing the concepts of guardianship in Islamic law, the Compilation of Islamic Law (KHI), and Law Number 1 Year 1974 on Marriage. The results show that the principle of guardianship in the Indonesian marriage legal system is based on the strong influence of Islamic law, especially in KHI. The marriage guardian is considered as a representation of honor and protection of women. However, there is also ambiguity in guardianship arrangements between the national legal system and social religious practices, which can lead to legal uncertainty. There is a need for harmonization between religious principles and human rights principles in marriage law, especially regarding women's autonomy in choosing a life partner. Revisions to regulations relating to guardianship are also needed to emphasize the position of women as independent and protected legal subjects.